Pro Angular 6 - Freeman, Adam (Apress, 2018)
Get the most from Angular 6, the leading framework for building dynamic JavaScript applications. Understand the MVC pattern and the benefits it can offer. Best-selling author Adam Freeman shows you how to use Angular in your projects, starting from the nuts and bolts and building up to the most advanced and sophisticated features, going in-depth to give you the knowledge you need. Chapters include common problems and how to avoid them. What You'll Learn: Gain a solid architectural understanding of the MVC Pattern Create rich and dynamic web app clients using Angular 6 Use the ng tools to create and build an Angular project Extend and customize Angular 6 Test your Angular 6 projects What's New in This Edition: Revised for the features and changes in Angular 6 Covers @angular/cli, ng command line tools, and WebPack Includes HttpClient for simplified asynchronous HTTP requests Presents updates to pipes and localized text display.